Taxes and Corporate Finance: A Review - Graham, John R. (Review of Financial Studies, 2003)
This article reviews tax research related to domestic and multinational capital structure, payout policy, compensation policy, risk management, and organizational form. For each topic, the theoretical arguments explaining how taxes can affect corporate decision making and firm value are reviewed, followed by a summary of the related empirical evidence and a discussion of unresolved issues. Tax research generally supports the hypothesis that high tax rate firms pursue policies that provide tax benefits. Many issues remain unresolved, however, including understanding whether tax effects are of first-order importance, why firms do not pursue tax benefits more aggressively, and whether corporate actions are affected by investor-level taxes. Copyright 2003, Oxford University Press.